2012
DOI: 10.5830/cvja-2011-048
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma homocysteine and myocardial SPECT abnormalities in patients referred for suspected myocardial ischaemia

Abstract: BackgroundElevated plasma homocysteine level has emerged as a relatively newly recognised risk factor for coronary artery disease (CAD). However, reduction of plasma homocysteine levels in large prospective studies did not appear to reduce the risk for subsequent cardiac events. In this study, we investigated the association between plasma homocysteine levels and quantitative indices of myocardial perfusion SPECT imaging in patients referred for myocardial ischaemia.MethodsQuantitative myocardial perfusion SPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Hcy is a potentially cytotoxic amino acid that is synthesized during methionine metabolism. Several studies have identified that even mild hyperhomocysteinemia is associated with an increased risk of cardiovascular, and related vascular diseases, independently of classic risk factors [9][10][11][12]. The main detrimental effects of Hcy are probably on vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hcy is a potentially cytotoxic amino acid that is synthesized during methionine metabolism. Several studies have identified that even mild hyperhomocysteinemia is associated with an increased risk of cardiovascular, and related vascular diseases, independently of classic risk factors [9][10][11][12]. The main detrimental effects of Hcy are probably on vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Oudi et al [32] have demonstrated that elevated levels of Hcy are associated with a greater number of diseased arteries and, consequently, the severity of coronary artery disease. In addition, Ankrah et al [12] showed that there was a correlation between plasma Hcy level and the presence of myocardial perfusion defects in patients with coronary artery disease, especially those with multiple risk factors and multivessel infarction. In keeping with these findings, we detected that patients with SCF in all of three vessels had higher plasma levels of Hcy when compared to the controls and patients with SCF in one and two vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation